"المراحل العملية لإعداد القوائم المالية - دراسة حالة - الشركة زفت الجنوب عموري " - سالم, عازب أحمد; بوبكر, عموري; هاجر, سراوي (جامعة الوادي - University of Eloued, 2023)
"ان اعداد القوائم المالية يعتبر جزء هاما في المؤسسات الاقتصادية حيث تهدف القوائم المالية الي توفير صورة شاملة ومفصلة عن الاداء المالي للشركة خلال فترة زمنية محددة، وتشمل القوائم الرئيسة مثل قائمة الدخل المركز المالي، قائمة التدفقات النقدية، وقائمة التغير في الاموال الخاصة. وايضا يجب مراعاة العديد من الامور عند القوائم المالية مثل استخدام المعايير المحاسبية المتعرف بها دوليا لتأكد من توفير المعلومات المالية الدقيقة والشفافة، كما يحب الافصاح عن جميع المعلومات الهامة بصورة كاملة وصحيحة والالتزام بالسياسات والاجراءات المحاسبية الداخلية، كما يعتبر التحليل المالي والمراجعة الدورية للقوائم المالية أما هاما حيث يساعد في تحقيق الشفافية والمصداقية والموثوقية فب المعلومات المالية. ونظرا لاختلاف اسس القياس والافصاح شكل صعوبة في فهم الاستغلال وقراءة المعلومات المحاسبية من قبل المستخدمين ادى الى اصدار المعايير الدولية للقوائم المالية لأزالة العوائق من خلال تقليل العوائق والفجوة الموجودة بين الانظمة المحاسبية وتلبيه إحتياجات متخذي القرارات على المستوى الدولي. " "Preparing financial statements is an important part of economic institutions, as the financial statements aim to provide a comprehensive and detailed picture of the company's financial performance during a specific period of time, and include the main lists such as the income statement, the financial position, the statement of cash flows, and the list of changes in private funds. Also, many matters must be taken into account when the financial statements, such as the use of internationally recognized accounting standards to ensure the provision of accurate and transparent financial information, and all important information must be fully and correctly disclosed and adherence to internal accounting policies and procedures. Financial analysis and periodic review of the financial statements are also important. It helps in achieving transparency, credibility and reliability in financial information. Due to the different bases of measurement and disclosure, the difficulty in understanding the exploitation and reading accounting information by users led to the issuance of international standards for financial statements to remove obstacles by reducing the barriers and gaps between accounting systems and meeting the needs of decision-makers at the international level."
Keywords: المراحل العملية - القوائم المالية- الشركة زفت الجنوب عموري; Practical stages - financial statements - the company asphalt south Amouri